Damage to Orbitofrontal Areas 12 and 13, but Not Area 14, Results in Blunted Attention and Arousal to Socioemotional Stimuli in Rhesus Macaques - Murphy, Lauren E.; Bachevalier, Jocelyne (Frontiers in Behavioral Neuroscience, 2020)
An earlier study in monkeys indicated that lesions to the mid-portion of the ventral orbitofrontal cortex (OFC), including Walker’s areas 11 and 13 (OFC11/13), altered the spontaneous scanning of still pictures of primate faces (neutral and emotional) and the modulation of arousal. Yet, these conclusions were limited by several shortcomings, including the lesion approach, use of static rather than dynamic stimuli, and manual data analyses. To confirm and extend these earlier findings, we compared attention and arousal to social and nonsocial scenes in three groups of rhesus macaques with restricted lesions to one of three OFC areas (OFC12, OFC13, or OFC14) and a sham-operated control group using eye-tracking to capture scanning patterns, focal attention and pupil size. Animals with damage to the lateral OFC areas (OFC12 and OFC13) showed decreased attention specifically to the eyes of negative (threatening) social stimuli and increased arousal (increased pupil diameter) to positive social scenes. In contrast, animals with damage to the ventromedial OFC area (OFC14) displayed no differences in attention or arousal in the presence of social stimuli compared to controls. These findings support the notion that areas of the lateral OFC are critical for directing attention and modulating arousal to emotional social cues. Together with the existence of face-selective neurons in these lateral OFC areas, the data suggest that the lateral OFC may set the stage for multidimensional information processing related to faces and emotion and may be involved in social judgments.